Handover training in the workplace: having a CHAT. (28th September 2018) - Moore, Malcolm; Roberts, Chris
Summary: Background: Clinical handover is a core skill that needs to be learned by students and junior clinical staff to improve patient safety. Despite this, training is frequently lacking and of poor quality. A user‐friendly assessment tool can assist clinicians to provide training and feedback. Context: This tool was developed in the context of medical students on short placements in remote health services, supervised by registered nurses, in outback Australia. Students make telephone handover calls to the Royal Flying Doctor Service (RFDS), which provides generalist and aeromedical retrieval services to its communities. Methods: Doctors in the RFDS at Broken Hill used a clinical handover assessment tool (CHAT), based on the introduction, situation, background, assessment and recommendation (ISBAR) handover mnemonic, for assessment and training on telephone handovers given by medical students in this remote setting. Medical students were invited to complete surveys and doctors completed interviews about their experience of giving or receiving handovers. Students highly valued the experience of learning handovers in a clinical setting. Doctors in the RFDS found the tool helpful for assessment and for giving feedback in their routine work. We identified no concerns about the safety of patients or students. …we explored the acceptability and educational impact of doctors giving immediate feedback on medical students' handover skills using CHAT Conclusions: We suggest that work‐based handover assessment and feedback provided by clinicians are feasible and should be developed further. Students can learn to give handovers safely even in a remote setting. Clinicians may find CHAT helpful in the learning and teaching of structured handovers in other clinical settings.